Increased Performances of the Biological Diagnosis of the Antiphospholipid Syndrome by the Use of a Multiplex Assay - M. Sénant; H. Rostane; F. Fernani-Oukil; F. Hosking; F. Bellery; A. Courchinoux; E. Tartour; L. Darnige; M-A. Dragon-Durey (Journal of Immunology Research)
Antiphospholipid syndrome (APS) is characterized by development of venous and/or arterial thrombosis and pregnancy morbidity. Biological criteria are the persistent presence of lupus anticoagulant (LA) and/or anti-cardiolipin (aCL) and/or anti-B2GP1 autoantibodies’ positivity. The assays’ performances are of crucial importance. We evaluated a multiplex assay allowing simultaneous detection of IgG anti-cardiolipin, anti-B2GP1, and anti-factor II. 300 samples were tested. Patients were categorized according to clinical scores of APS from 0 to 3 based on presence or not of arterial or venous thrombosis, fetal loss, and autoimmunity. We used a multiplex assay for APS for simultaneous detection of aCL, anti-B2GP1, and factor II and compared its performances to ELISA assays. Presence of LA was also assessed. We performed a correlation study of the tested assays and compared their clinical efficacy by ROC curve analysis. We obtained significantly higher performances with the multiplex assay than ELISA with higher area under the curve (AUC). The disease rate increased with the number of positive markers from 9% for 1 marker to 100% for 4 markers positive for patients with high risk scores. The multiplex APS assay exhibited higher performances particularly in case of primary APS and is useful for rapid diagnosis of APS.